Original paper High-dose-rate brachytherapy boost for prostate cancer: rationale and technique - Morton, Gerard C. (Journal of Contemporary Brachytherapy, 2014)
High-dose-rate brachytherapy (HDR) is a method of conformal dose escalation to the prostate. It can be used as a local boost in combination with external beam radiotherapy, with a high degree of efficacy and low rate of long term toxicity. Data consistently reports relapse free survival rates of greater than 90% for intermediate risk patients and greater than 80% for high risk. Results are superior to those achieved with external beam radiotherapy alone. A wide range of dose and fractionation is reported, however, we have found that a single 15 Gy HDR combined with hypofractionated radiotherapy to a dose of 37.5 Gy in 15 fractions is well tolerated and is associated with a long term relapse-free survival of over 90%. Either CT-based or trans-rectal ultrasound-based planning may be used. The latter enables treatment delivery without having to move the patient with risk of catheter displacement. We have found it to be an efficient and quick method of treatment, allowing catheter insertion, planning, and treatment delivery to be completed in less than 90 minutes. High-dose-rate boost should be considered the treatment of choice for many men with high and intermediate risk prostate cancer.